Pelatihan Pengajaran Bahasa Inggris Dasar Menggunakan Metode TPR (Total Physical Response) sebagai Solusi Pembelajaran bagi Guru TK di KB/TK Nasrullah - Asfar, Shafira; Saputri, Tiyas; Al Ayubi, M. Sholahuddin; Ramadina, Silviana; Ridza, Nurisma Ilfidzatur; Annuri, Farhat Muharrom (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Choosing the right English learning method for early childhood is very important. At an early age, children's development is in a concrete phase. Therefore, the learning process applied to early childhood education must be based on something real or tangible in accordance with the learning objectives, which is to convey basic concepts that have meaning through real experiences, in order to enhance the creativity, memory, and curiosity of the child. The Community Service Program (PKM) involves a series of structured stages. First, observation and survey of the location where the PKM activities will be carried out to ensure all necessary preparations. As a plan to fully implement this activity, it will be divided into two parts. First, a final evaluation will be conducted on the training that has taken place. The final step is to prepare a final report summarizing the entire program journey, including objectives, methods, findings, and recommendations for the future.